2016
DOI: 10.1371/journal.pone.0155854
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiological, Clinical and Antiretroviral Susceptibility Characterization of Human Immunodeficiency Virus Subtypes B and Non-B in Pernambuco, Northeast Brazil

Abstract: BackgroundHIV-1 diversity causes important differences in the virus’ biological properties and their interactions with hosts, such as cell tropism, responses to antiretroviral therapy, drug-resistance, and disease progression.ObjectivesWe evaluated the interrelationship of phylogenetic inference with epidemiological and laboratory data for HIV-1 isolates circulating in Pernambuco, Northeast Region—Brazil.Study designA total of 168 HIV-1 pol sequences were analysed, 64 were obtained from 2002–2003, and 104, fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
1
2
0
2
Order By: Relevance
“…Our findings showed that subtype B had a lower median CD4 T-cell count compared to subtypes F1 and C, as also recorded in previous studies ( 24 ), however, that comparison revealed no differences in viral load levels between the HIV-1 subtypes. This study has not performed any survival analyses on the three subtypes, though other authors have suggested an association between the viral subtype and progression to AIDS ( 25–28 ).…”
Section: Discussionsupporting
confidence: 90%
“…Our findings showed that subtype B had a lower median CD4 T-cell count compared to subtypes F1 and C, as also recorded in previous studies ( 24 ), however, that comparison revealed no differences in viral load levels between the HIV-1 subtypes. This study has not performed any survival analyses on the three subtypes, though other authors have suggested an association between the viral subtype and progression to AIDS ( 25–28 ).…”
Section: Discussionsupporting
confidence: 90%
“…We observed that the salvage therapy regimen was predominantly composed of PI/r and NRTI(t)s, with virologic success in most cases. Subtype B remains the most common in Pernambuco [ 17 19 ] and in Brazil [ 11 ], except in the south, where subtype C [ 21 ] is predominant. There has been an increase in the proportion of recombinant forms in Rio de Janeiro [ 22 ] and subtype F in Minas Gerais [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In HIV-1 subtype B, two-thirds of the clusters networks were composed of male patients (6/9), with no information about of sexual exposure. Another study in Northeast Brazil [29] showed a higher number of men who have sex with men infected with HIV-1 subtype B when compared with non-B subtypes, nevertheless without statistical significance (p = 0.06).…”
Section: Discussionmentioning
confidence: 95%